The Relation between Creativity, Identity and Political Expression in the Writings of Gabriel Garcia Marquez and Shahnon Ahmad (Malay Literature, 2014)
The presence of political elements within literary works is often seen as something provocative. Through a framework proposed by C. R. Rogers in his essay entitled "Towards a Theory of Creativity", this article will demonstrate the close link between an author, his creativity and the political theme in the creation of his literary works. This framework enables the author's personal attributes and personality to be linked to the political elements featured in his works. The creativity of a political novelist is found to be dependent on his surroundings, experience and political awareness. In relation to this, two authors of political novels are highlighted in this research. They are Shahnon Ahmad (Malaysia) who produced Tunggul-Tunggul Gerigis and Gabriel Garcia Marquez (Latin America) famed for his work One Hundred Years of Solitude. It is discovered through this research that the two political novelists did not write in a vacuum. The presence of political subjects specifically mentioned in their works clearly originates from their real-life surroundings which have consolidated into their identity, personality and authorship as political writers. In other words, politics is the authors' flesh and blood and this allows political subjects to be crafted and expressed in their creative works. Hence an author without a varied background in politics will never be able to create or produce effective political works or novels.Keyword: political novel, creativity, myths, authorship, comparative literature